2020
DOI: 10.1111/jvec.12387
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the chemical ecology of mosquito oviposition behavior in mosquito surveillance and control: a review

Abstract: Vector control is an important component of the interventions aimed at mosquito‐borne disease control. Current and future mosquito control strategies are likely to rely largely on the understanding of the behavior of the vector, by exploiting mosquito biology and behavior, while using cost‐effective, carefully timed larvicidal and high‐impact, low‐volume adulticidal applications. Here we review the knowledge on the ecology of mosquito oviposition behavior with emphasis on the potential role of infochemicals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 255 publications
(276 reference statements)
2
34
0
1
Order By: Relevance
“…More than 100 attractive substances have been found, as reported in the literature. However, they are not selective, have efficacy limited to specific environmental conditions [90,91], and, overall, no information is available about their effect on trap competitiveness against natural breeding sites.…”
Section: Biomimetic Approach As a Possible Solution To The Limits Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 100 attractive substances have been found, as reported in the literature. However, they are not selective, have efficacy limited to specific environmental conditions [90,91], and, overall, no information is available about their effect on trap competitiveness against natural breeding sites.…”
Section: Biomimetic Approach As a Possible Solution To The Limits Of ...mentioning
confidence: 99%
“…Mosquito oviposition is a complex and multifactorial event requiring selection of the egg-laying site during which the gravid female, guided by several stimuli, identifies the most suitable site for the offspring's survival [91]. Given the extreme adaptability of A. albopictus at the larval level [77], both in natural and in anthropised contexts of different geographical areas, many signals (e.g., surface features, volatile compounds from decaying vegetal matter and microbial community, site/background colour, adequate pH and salinity, presence of conspecific larvae or predators [40]) play a role in identifying microenvironments for site selection [98][99][100][101][102].…”
Section: Specialisation Of the Biomimetic Lure-and-kill Approach To P...mentioning
confidence: 99%
“…In addition, the alignment of amino acid sequences indicated that Or11 was conserved among three major disease-transmitting vectors: Anopheles , Culex , and Aedes (Additional file 1 : Figure S1). Such conserved and female-biased odorant receptors as Or11 should be significant for the olfactory system in mosquitoes; thus, we deorphanized AalbOr11 in Xenopus oocytes by a panel of odorants with physiologically and behaviorally relevant compounds, including human-related odorants, oviposition attractants, and plant repellents [ 13 , 28 , 42 ]. The expression profiles of AalbOr11 among different sexes, ages, and physiological states were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti oviposition (Benzon and Apperson, 1988; Ponnusamy et al, 2008; Melo et al, 2020). Indeed, females can locate suitable breeding sites using infochemicals emitted by microbes inhabiting the aquatic niche (Mwingira et al, 2020). This choice is probably under selection pressure because microorganisms within oviposition containers not only represent food to the larvae but can also establish intricate host-bacterial community networks eventually defining a symbiotic relation (Ponnusamy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%